Compatibilidad del hongo entomopatógeno Purpureocillium sp. cepa UdeA0106 con biocontroladores y productos fitosanitarios utilizados en cultivos de crisantemo (2014)
ABSTRACT: The entomopathogenic fungus Purpureocillium sp. strain UdeA0106 was isolated in soil from a farm belonging to the Universidad de Antioquia. This fungus has shown potential in vitro and under greenhouse conditions to control symphylans (Scutigerella sp.) , a pest that attacks chrysanthemum crops, whose control has been achieved with the use of some insecticides, which temporarily reduce populations but without the desired ef ciency throughout the cultivation cycle. Currently the Purpureocillium sp. strain UdeA0106 is applied in combination with another biocontrol fungi, fungicides and insecticides in the integrated pest management systems (IPM) for chrysanthemum crops (eastern Antioquia); however, the ecological aspects related to the compatibility of the fungus Purpureocillium sp. strain UdeA0106 and the control strategies are unknown. The goals of the present study were to evaluate the in vitro antagonism of Purpureocillium sp. strain UdeA0106, with the biocontroller Paecilomyces lilacinus (Samson 1974), Beauveria bassiana (Vuill. 1912), Metarhizium anisopliae (Sorokīn 1883) and Trichoderma viride (Pers. 1794), using the dual plates method, and to study the effect of plant protection products applied regularly in ower crops on Purpureocillium sp. strain UdeA0106, under laboratory conditions. The results obtained demonstrated that the fungus Purpureocillium sp. strain UdeA0106 showed in vitro compatibility with the majority of the biocontrol fungi, except with Trichoderma viride. The fungicide Carbovax® (carboxin + thiram) completely inhibited germination and vegetative growth of the fungus. The advances in the understanding of the compatibility of this fungus with other products commonly applied on ower crops will enable in the future a more ef ciently use of the fungus Purpureocillium strain UdeA0106, to control this pest in chrysanthemum crops.